2011
DOI: 10.1128/mbio.00071-11
|View full text |Cite
|
Sign up to set email alerts
|

Competence in Streptococcus pneumoniae Is Regulated by the Rate of Ribosomal Decoding Errors

Abstract: Competence for genetic transformation in Streptococcus pneumoniae develops in response to accumulation of a secreted peptide pheromone and was one of the initial examples of bacterial quorum sensing. Activation of this signaling system induces not only expression of the proteins required for transformation but also the production of cellular chaperones and proteases. We have shown here that activity of this pathway is sensitively responsive to changes in the accuracy of protein synthesis that are triggered by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
103
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(121 citation statements)
references
References 55 publications
(58 reference statements)
16
103
2
Order By: Relevance
“…In addition to its sensitivity to bacterial density, we have recently shown that pneumococcal competence is triggered when the frequency of biosynthetic errors during protein translation increases (8). Such responsiveness to the accuracy of protein synthesis supports the recent suggestion that competence in S. pneumoniae serves as a stress response (9) and is consistent with the observation that the competence regulon includes genes for cellular proteases and chaperones in addition to those genes responsible for transformation (10).…”
supporting
confidence: 68%
See 4 more Smart Citations
“…In addition to its sensitivity to bacterial density, we have recently shown that pneumococcal competence is triggered when the frequency of biosynthetic errors during protein translation increases (8). Such responsiveness to the accuracy of protein synthesis supports the recent suggestion that competence in S. pneumoniae serves as a stress response (9) and is consistent with the observation that the competence regulon includes genes for cellular proteases and chaperones in addition to those genes responsible for transformation (10).…”
supporting
confidence: 68%
“…Such responsiveness to the accuracy of protein synthesis supports the recent suggestion that competence in S. pneumoniae serves as a stress response (9) and is consistent with the observation that the competence regulon includes genes for cellular proteases and chaperones in addition to those genes responsible for transformation (10). Although the underlying mechanism has not been defined, this error-dependent pattern of regulation is generated in part through the activity of the bacterial HtrA protease, which acts selectively to repress the development of competence when the frequency of translational errors is low (8).…”
mentioning
confidence: 53%
See 3 more Smart Citations